The Theology of Struggle: Critiques of Church and Society in the Philippines (1970s-1990s) - Lisa Asedillo (Indonesian Journal of Theology, 2021)
This article explores writing and scholarship on the theology of struggle developed by Protestants and Catholics in the Philippines during the 1970s-90s. Its focus is on popular writing—including pamphlets, liturgical resources, newsletters, magazines, newspaper articles, conference briefings, songs, popular education and workshop modules, and recorded talks—as well as scholarly arguments that articulate the biblical, theological, and ethical components of the theology of struggle as understood by Christians who were immersed in Philippine people’s movements for sovereignty and democracy. These materials were produced by Christians who were directly involved in the everyday struggles of the poor. At the same time, the theology of struggle also projects a “sacramental” vision and collective commitment towards a new social order where the suffering of the masses is met with eschatological, proleptic justice—the new heaven and the new earth, where old things have passed away and the new creation has come. It is within the struggle against those who deal unjustly that spirituality becomes a “sacrament”—a point and a place in time where God is encountered and where God’s redeeming love and grace for the world is experienced.